Thorough branding strategy analysis of Nestlé Dairy Brands in Bangladesh - Ferdosi, Kazi Humaira (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.